Evaluation of diagnostic and remedial aspects of a microcomputer program on speed - Zietsman, Aletta Isabella (My University, 2014)
This study is an evaluation of the remedial and diagnostic components of a microcomputer program on speed. The program is based on a conceptual change model developed within the field of cognitive science research. The influence of research in cognitive science on the current research in science education is discussed as well as recent research in the field of kinematics in the context of science education. The literature relevant to the study is reviewed, and the design of the study and the evaluation procedures are described. The results of the investigation are presented and analysed and finally conclusions from these findings are presented.
Keywords: Education--South Africa--Data processing